AVALIAÇÃO DAS ATIVIDADES ANTIOXIDANTE, ANTIMICROBIANA E CITOTÓXICA DE PSYCHOTRIA NUDA (CHAM. & SCHLTDL.) WAWRA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
The medicinal plants study has led to the discovery of pharmacologically active substances. The species Psychotria nuda (Cham. and Schltdl.) Wawra is a shrubby plant distributed in the Atlantic Forest at the east coast of Brazil and haven’t phytochemical studies and no description of their biological activities until the present moment. This study evaluated the antimicrobial, antioxidant and cytotoxic activity. The hydroalcoholic extract showed no antimicrobial activity against strains of Staphylococcus aureus, Escherichia coli and Candida albicans. However, in antioxidants tests, the extract showed antioxidant action scavenger of cationic radical ABTS+ (IC50: 33,48 ± 1,99 g/mL), and was able to reduce lipid peroxidation induced by AAPH radical on erythrocytes (IC50: 31,59 ± 4,14 g/mL for 3 hours incubation) without cytotoxic effect in these cells. It showed a moderate antioxidant activity of hypochlorous acid (IC50: 359,24 ± 4,57 g/mL) and reduced activity to scavenger DDPH radical (IC10: 118,76 ± 28,83 g/mL), superoxide anion (IC15: 196,92 ± 0,270 g/mL), and the enzymatic oxidation induced by HRP (IC20: 104,15 ± 18,15 g/mL). We observed high cytotoxicity assessment models of cell viability by MTT in epithelial HaCaT cells (CL50: 7,72 ± 1,22 g/mL) and a moderate citotoxicity for the strain of mouse embryonic fibroblast NIH3T3 (CL50: 61,65 ± 5,12 g/mL). In assay of neutral red dye incorporation in both lineage cells, we observed a high cytotoxicity in HaCaT cells (CL50: 6,07 ± 0,79 g/mL), but no effect of the extract over NIH3T3 cells at the used concentrations. The extract showed potential antioxidant and cytotoxic activity, and evaluation of crude extract allow us to conducting further research to identify the biologically active molecules
Keywords: Psychotria nuda; antioxidante; antimicrobiano; citotoxicidade; Psychotria nuda; antioxidant; antimicrobial; cytotoxicity; CNPQ::CIENCIAS DA SAUDE::FARMACIA